A case of laryngeal tuberculosis mimicking supraglottic carcinoma in a pregnant patient and literature review: Laryngeal tuberculosis mimicking supraglottic carcinoma - Baklacı, Deniz; Cakir Turhan, Anil; Harma, Müge (Journal of Surgery and Medicine, 2023)
Tuberculosis (TB) is the most common granulomatous disease, but laryngeal involvement is rare. The risk of developing this clinical form is higher in immunocompromised patients due to primary infection or reactivation of latent TB. Laryngeal TB can be misdiagnosed as laryngeal cancer since they have similar macroscopic lesions, and both cause dysphonia. We present a case of laryngeal TB in a 37-week pregnant patient who complained of dysphonia, odynophagia, and dysphagia. A mass with supraglottic carcinoma findings was discovered during a laryngoscopic examination. The reason for presenting this case is to emphasize the necessity for a high degree of suspicion for laryngeal TB involvement in patients with upper respiratory tract lesions in regions with high TB prevalence, to achieve early diagnosis and treatment.